O uno e o ser no pensamento de Meister Eckhart - Raschietti, Matteo [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Filosofia, 2012)
O problema de fundo da especulação eckhartiana é a verdade do ser uno enquanto Deus e divino ligada à questão do seu conhecimento. Operando uma síntese da tradição neoplatônico-agostiniana e do pensamento do Pseudo-Dionísio Areopagita, o mestre dominicano funda os alicerces da sua teologia unitiva na teoria do ser.

The fundamental problem of Eckhartian speculation is that of the connection between the truth of the unique being as God and the question of His knowledge. By creating a synthesis of the Augustinian-Platonic tradition and the thought of Pseudo-Dionysius the Areopagite, the Dominican master founds the basis of his unitary theology in the theory of being.
Being and the one in the thought of Meister Eckhart
Keywords: Uno; Ser; Conhecimento; Analogia; Causalidade; One; Being; Knowledge; Analogy; Causality